ANALISIS KELAYAKAN UKM AGRIBISNIS BERBAHAN UMBI-UMBIAN DI KOTA BATURAJA (JASEP, 2019)
UKM is a businessunit that is managed community grup and families that the majority of business. Tubers are one of the agricultural commodities that can be used as food sources such as potatoes and sweet potatoes. Utilization of food materials lokol can be improved through the development of processed products. From snack farming commodies in the form of chips is the type of food that is most high demand market sharethat has greater chips in comparison, and also in terms of rate of capital faster with the rate of spider which is also higher. A feasibility study of tubers consisting of potatoes and sweet potatoes is a business that not only analyzes whether or not the basiness is built up but also for the achievement of maximum profit for an unspecified time.